SPT13 (GAL11) of Saccharomyces cerevisiae negatively regulates activity of the MCM1 transcription factor in Ty1 elements. - Yu, G (1993)
The Ty transposable elements of Saccharomyces cerevisiae consist of a single large transcription unit whose expression is controlled by a combination of upstream and downstream regulatory sequences. Errede (B. Errede, Mol. Cell. Biol. 13:57-62, 1993) has shown that among the downstream control sequences is a binding site for the transcription factor, MCM1. A small restriction fragment containing the Ty1 MCM1-binding site exhibits very weak activation of heterologous gene expression. The absence of SPT13 (GAL11) causes a dramatic increase in activity directed by these sequences. This effect is mediated through the MCM1-binding site itself. MCM1 mRNA and protein levels, as well as its affinity for its binding site, are unchanged in the absence of SPT13. Our results suggest that SPT13 has a role in the negative control of MCM1 activity that is likely to be posttranslational. A role for SPT13 in the negative regulation of the activity of the Ty1 MCM1-binding site is consistent with our previous proposal that spt13-mediated suppression of Ty insertion mutations could be attributed to the loss of negative regulation of genes adjacent to Ty elements.